Prevalence of respiratory diseases in thoroughbreds racing in Perak Turf Club, and their association with performance upon surgical correction - Ridzuan, Nur Aisyah (2016)
In equine athletes, respiratory diseases affecting either the upper or lower airways or both are common and they have been identified as an important cause of poor performance in horses. The prevalence of lower airway diseases is high in equine athletes, but the prevalence of upper airways disorders is difficult to be determined since these conditions are not necessarily evident during examination at rest. This study focuses mainly on the prevalence of respiratory diseases in Thoroughbreds racing in Perak Turf Club between year 2011 to 2015, and how they impair race performance. The horses’ racing performance is compared using cross-sectional study between those that underwent surgery and those without surgical correction. Respiratory diseases with the highest case recorded was exercise induced pulmonary haemorrhage (EIPH) Grade 1 or respiratory distress (38.2%), followed by EIPH Grade 2 (30.2 %), recurrent airway obstruction (RAO) with 17.6 %, epiglottic entrapment and other conditions with 4.0 % respectively and 3.0 % for both dorsal displacement of soft palate (DDSP) and respiratory noises. There is no significant association between racing performance following surgery, in which it can be concluded that surgical corrections does not assure improvement in equine performance.